(untitled) (Acta Polytechnica CTU Proceedings, 2024)
A novel interface to provide robust, intuitive, and timely alerts to road users to move over for emergency vehicles (EVs) was tested in a seven-minute driving-simulator experiment. The interface, Augmented Emergency Lighting (AEL), mimics emergency lighting on emergency vehicles (i.e., flashing blue light), by using the cars’ interior lighting. AEL was initiated 30 seconds before an EV caught up and increased its brightness proportionally to the distance to the EV. The AEL alert was after 16 seconds accompanied by an Emergency Vehicle Approaching (EVA) alert, presented as a voice command and a text message on the dashboard. Comparisons were made between AEL+EVA alerts, EVA-only alerts, and no alerts, between groups (N = 61). Both AEL+EVA alerts and AEL-only alerts were highly successful in getting drivers to move over by slowing down and pulling off to the side as compared to when there were no alerts, but no significant difference between AEL+EVA and EVA-only was found. Questionnaire responses showed that AEL+EVA alerts were generally appreciated and that their timing was good. Further studies on learning effects and usability are discussed.